Muslim Attitude Towards Participation In Cash Waqf: Antecedents And Consequences - Shukor, SA; Anwar, IF; Aziz, SA; Sabri, H (Univ Malaysia Sarawak, Fac Economics & Business, 2024)
Indexed by WOS/ Scopus